2018
DOI: 10.1002/mp.12972
|View full text |Cite
|
Sign up to set email alerts
|

Automated patient‐specific transperineal ultrasound probe setups for prostate cancer patients undergoing radiotherapy

Abstract: Provided that the ultrasound probe setup proposed by the algorithm, is properly reproduced on the patient, it allows visualization of all clinically required structures for image guided radiotherapy purposes. Future work should validate these results on a patient population and optimize the workflow to enable a relatively untrained operator to perform the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, at patient set up, the probe must be manually adjusted to ensure both reproducible positioning and adequate target volume coverage. Approaches to assist with probe-positioning are being investigated (Camps et al 2017 , 2018 ). Remote probe support and robotic systems are also being developed to optimise probe placement during both patient set up and treatment delivery (Schlosser et al 2012 , Sen et al 2017 , Su et al 2017a ).…”
Section: Real-time Intrafraction Motion Monitoring Methodsmentioning
confidence: 99%
“…Furthermore, at patient set up, the probe must be manually adjusted to ensure both reproducible positioning and adequate target volume coverage. Approaches to assist with probe-positioning are being investigated (Camps et al 2017 , 2018 ). Remote probe support and robotic systems are also being developed to optimise probe placement during both patient set up and treatment delivery (Schlosser et al 2012 , Sen et al 2017 , Su et al 2017a ).…”
Section: Real-time Intrafraction Motion Monitoring Methodsmentioning
confidence: 99%
“…Accuracy of prostate volume measurements using TPUS has previously been validated against trans-rectal ultrasound and found to be an accurate and less invasive alternative imaging method [13]. Recently, emerging evidence reported by Camps et al [14] has also demonstrated how TPUS images can value-add visualisation of anatomical structures (e.g. prostate, bladder, rectum) within the pelvic region of prostate cases.…”
Section: Values Of Ct/tpus Imagesmentioning
confidence: 99%